Public relation digital sebagai strategi manajemen pemasaran di industri perbankan syariah - Fauziyah, Tatia Nur (Maliki Interdisciplinary Journal, 2025)
Digital transformation has brought significant changes in the Islamic banking industry, so it demands an adaptive and relational communication strategy. This study aims to analyze the role of digital Public Relations as a strategy in marketing management in the Islamic banking industry. The research method used is qualitative with a literature study approach, so that it can provide a conceptual framework on how digital Public Relations contributes to building a positive image, reputation, and customer loyalty. The results of the study show that digital Public Relations not only functions as a promotional tool, but also as a medium for education and strengthening public trust through the use of online media such as websites, social media, and mobile banking applications. This strategy is effective in improving Islamic financial literacy and can expand market reach and strengthen the competitive position of Islamic banks in the midst of competition in the modern banking industry. Thus, the synergy between Public Relations and marketing management is a key factor for the sustainability and competitiveness of Islamic banking in the digital era.